Uji Aktivitas Antifungi Ekstrak Daun Sirih (Piper betle L) terhadap Saprolegnia sp. Secara In Vitro [Antifungal Activities Test Of Betel Leaf Extract (Piper betle L) On Saprolegnia sp. By In Vitro] - Rahayu Kusdarwati; Dewa Ketut Meles; Ayu Ratnaningtyas (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Saprolegniasis is a mycotic disease caused by Saprolegnia sp. that usually attacking wild fish and farming fish. Saprolegnia sp. cause a lot of harm in process of the fish cultivation. Prevention and treatment of the common practice is use chemical drugs, but the use of these chemicals tend to be environmentally unfriendly and there are has karsinogenik effect. Therefore, the use of traditional medicines is one of alternative to control Saprolegnia sp. safer than chemical drugs. Green betel leaf contains phenolic compounds and tannins are efficacious as antifungal agent. This study aims to prove the antifungal activity of extracts of betel leaf (Piper betle L) for Saprolegnia sp., and to know the minimum concentration of betel leaf extract (Piper betle L) as antifungal for Saprolegnia sp. The design of this experiment is used completely randomized design (CRD) with 11 treatments and 3 replications. This study used the dilution method through the Minimum Inhibitory Concentration determination (MIC) and Minimum Fungicidal Concentration (MFC). The concentration of the extract used was 50% (0.5 g/ml), 25% (0.25 g/ml), 12.5% (0.125 g/ml), 6.25% (0.0625 g/ml), 3.13% (0.0313 g/ml), 1.56% (0.0156 g/ml), 0.78% (0.0078 g/ml), 0.39% (0.0039 g/ml), 0.2% (0.002 g/ml) of betel leaf extract. A positive control containing 2 ml of 3% hydrogen peroxide were added fungal suspension until 4 ml Negative control containing 2 ml of 10% DMSO were added fungal suspension until 4 ml. The main parameters in this study is the value of optical density (OD) for MIC (Minimum Inhibitory Concentration) test and the absence of Saprolegnia sp. growing on SDA media for MFC (Minimum Fungicidal Concentration) test. 0.20% (0.002g/ml) concentration of of betel leaf extract is the minimum concentration that can inhibit the growth of Saprolegnia sp. MFC test results showed concentrations of 0.78% (0.0078 g/ml) betel leaf extract is the minimum concentration that can kill Saprolegnia sp.